The influence of knowledge, attitude and skills on conscious behavior in women of fertilizing age in Bandar Baru district Pidie Jaya - Mufida, Nurlela; Iklima; Mu'alim, Azhar; Ismuntania; Rospita (Trigin Institute, 2024)
Breast self-examination (BSE) is the easiest and most effective way to find lumps and other signs, so it is hoped that it will be able to reduce the death rate by 25-30%. This study aims to determine the influence of knowledge, attitudes and skills on BSE behavior in women of childbearing age (WUS). The research method uses analytical methods with a cross-sectional approach. The population in this study were all women of childbearing age (WUS) in the Baru sub-district totaling 1,159 people, the sampling technique in this study used starfed random sampling totaling 92 people. The results of this study show that there is no influence of the knowledge factor (0.194 > 0.05), there is an influence between the attitude factor (0.002 < 0.05), the skills factor (0.037 < 0.05) and BSE behavior in WUS. The conclusion of this research is that there is no influence of knowledge factors, there is influence of attitude factors and skills factors on BSE behavior in women of childbearing age (WUS) in Bandar Baru District, Pidie Jaya Regency. Advice to women of childbearing age (WUS) to be more open about doing BSE is also to be more productive in seeking information about breast health problems and visiting health services if they become aware of breast abnormalities